Frequency of chlamydia trachomatis ureaplasma urealyticum and mycoplasma hominis in endocervix of women during menacme - Frias, Márcia C.A.A.; Pereira, Cláudio F.A.; Pinheiro, Vandira M.S.; Pinheiro, Marcia S.; Rocha, Carolina F. (Brazilian Journal of Sexually Transmitted Diseases, 2001)
Bacteria with potential to be sexually transmitted, Chlamydia trachomatis, Ureaplasma urealyticum and Mycoplasma hominis, cause endocervicitis, and other types of infection of the urogenital tract. Complications, include endometritis, pelvic inflamatory diseases, bartholinitis, posterior uretritis, sterility and severe infection of newborns (neonates) through vertical transmission (from mother to fetus). Although highly prevalent, poor or absent symptomatology make these types of infection unfamiliar and consequently lacking treatment during their course. Their exact incidence remain unknow in our enveroxment, due to scarcity of surveys. Purposes: Determine the frequency of C. Trachomatis, U. urealyticum and M. hominis in endocervix of private gynecological clinics in the country of Teresópolis (State of Rio de Janeiro). Methodology: A prospective study of sexually active women between ages 13 and 49, surching gynecological treatment for diverse reasons was carried out, and none of them made use of oral or vaginal antimicrobials during the fifteen days that preceding consultation. The survey included anaminesis (story), gynecological examination, oncotic colpocytologic studies and endocervical detection of bacteria formerly named. Enzyme-linked immunosorbent assay (ELISA)- “Mini-Vidas” automatized system for C. Trachomatis and Biomerieux for M. hominis and U. urealyticum were used as detection methodology. Results: In a ample of 100 patients clamydial antigens were detected in 5 women (5%). The positivity for M. urealyticum was 33% and for M. hominis 4%. Conclusions: The higher incidence of U. Urealyticum (33%). The main reasons for medical consultation were routine visit and leucorrhea.